The Anatomical Basis and Clinical Progress of Pericapsular Nerve Block Technique for Hip Joint - he, junchu; Ye, Yumin; Sun, Anling (Pacific International Journal, 2026)
Objective: To systematically review the anatomical basis, clinical application effects, and research progress of pericapsular nerve group (PENG) block technique, providing reference for clinical analgesia plan selection. Methods: Relevant literature at home and abroad was searched, summarizing the anatomical characteristics and technical innovations of PENG block, comparing the limitations of traditional block techniques, analyzing its clinical analgesic effects, preservation of motor function, and safety, summarizing current controversies and looking forward to future directions. Results: PENG block is based on the multi-source nerve distribution (femoral nerve, obturator nerve, and accessory obturator nerve supply) and the separation characteristics of sensory-motor nerve pathways at the anterior capsule of the hip joint. Through ultrasound-guided targeted injection (with the puncture needle inclined at 30-45° to the midpoint of the line connecting the anterior inferior iliac spine and the pubic tubercle), sensory-motor separation block can be achieved. Clinical studies show that PENG block can reduce dynamic visual analog pain scores (Visual Analogue Scale, VAS) in patients with hip fractures (from 7.8 to 3.2), reduce morphine consumption by 45% in patients undergoing total hip arthroplasty (Total Hip Arthroplasty, THA) within 12 hours postoperatively, and achieve a quadriceps muscle strength retention rate of 92% at 6 hours post-THA, with a major complication rate of only 1.4%. Current controversies focus on differences in access methods (direct vision vs. ultrasound guidance) and drug parameters (optimizing local anesthetic concentration at 18-20mL), with long-term safety data still needing to be supplemented. Conclusion: PENG block has achieved precision in hip joint analgesia, highly aligning with the concept of enhanced recovery after surgery (Enhanced Recovery After Surgery, ERAS), and is a high-quality alternative to traditional block techniques. Future improvements in clinical value should be made through artificial intelligence-assisted positioning and multimodal analgesia integration.